Language and Content Outcomes of CLIL and EMI: A Systematic Review - Keith Mathew Graham; Yunkyeong Choi; Amin Davoodi; Shakiba Razmeh; L. Quentin Dixon (Universidad de La Sabana, 2018)
Around the world, language teachers are shifting to content-based instruction (CBI) as a way to teach English, most commonly in the form of Content and Language Integrated Learning (CLIL) or English-Medium Instruction (EMI). With the spread of CBI around the world, it is important to understand how this shift in teaching has affected student outcomes. Using a systematic literature review approach, this study examines current literature on the effect of CBI on language and content outcomes. Twenty-five articles met the inclusion criteria for this study and were examined. The results show mixed findings on the effectiveness of CBI on student outcomes, with the majority of studies showing either positive or neutral effects for CBI when compared with non-CBI classrooms. However, the study also reveals multiple methodological issues that cause difficulties for any strong conclusions about CBI to be made. In addition, while CLIL in Spain has received a lot of research attention, other countries remain understudied. Therefore, this study concludes with a call for future research of CBI outcomes that examine a variety of countries and account for the methodological flaws identified.